Modeling and Manufacturing of a Flexible Socket for Above-Knee Amputation Prosthesis - Hasan, Hala Salman; Abbas, Saif Mohammed; Mohammed, Salsabil K.; Ibraheem, Marwa Qasim (Engineering, Technology & Applied Science Research, 2025)
There is a high incidence of Above-Knee (AK) amputations in Iraq due to factors, such as war, birth defects, explosives, and accidents. The development of advanced prosthetic solutions is critical in improving the comfort and life quality of the amputees. Traditional prosthetic sockets for AK amputations often cause discomfort, limit mobility, and increase the risk of secondary health issues, such as scoliosis. Creating a socket that balances both support and flexibility for the amputee, addressing these concerns while also ensuring comfort and ease of use is a major challenge. The objective of this project is to design a prosthetic socket combining stiff and flexible materials to optimize comfort, support, and functionality for AK amputees. The goal is to develop a socket that alleviates back discomfort, reduces the risk of scoliosis, and improves suspension while being easier to wear and more aesthetically pleasing. This project employs a composite material approach, using a combination of silicon, carbon, perlon, and laminate to create the socket. The socket is designed in two parts: the first part utilizes rigid materials to support the weight of the amputee, while the second part incorporates flexible materials to allow for muscle movement during gait. Tensile tests were conducted to determine the mechanical properties of silicon with perlon, and the performance of the flexible socket was evaluated in terms of pressure distribution and comfort. The tensile testing of silicon with perlon yielded a Young’s modulus of 0.0165 GPa, a yield strength of 0.283 MPa, and an ultimate tensile strength of 1.386 MPa. Additionally, the maximum F-socket pressure measured in the anterior region was 490 kPa.